2011
DOI: 10.1139/z11-079
|View full text |Cite
|
Sign up to set email alerts
|

Changes in relative abundance of snowshoe hares (Lepus americanus) across a 265-year gradient of boreal forest succession

Abstract: Understory regeneration within canopy gaps in old-growth boreal forests may provide suitable habitat for wildlife typically associated with early-seral stages, leading to an increase in their abundance in late succession. We surveyed a chronosequence of postfire (17-265 years) and postharvest (3-63 years) stands in Canada's eastern boreal forest to determine whether snowshoe hares (Lepus americanus Erxleben, 1777) followed a bimodal abundance distribution with stand age that reflects changes in food and cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 57 publications
(91 reference statements)
6
37
1
Order By: Relevance
“…However, a similar bimodal pattern of pellet densities was reported in eastern Quebec by Hodson et al (2011). Although Hudson et al (2011) did not measure deadfall, its association with more in tensively used canopy gaps in older growth stands seems likely (J.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…However, a similar bimodal pattern of pellet densities was reported in eastern Quebec by Hodson et al (2011). Although Hudson et al (2011) did not measure deadfall, its association with more in tensively used canopy gaps in older growth stands seems likely (J.…”
Section: Discussionsupporting
confidence: 57%
“…For example, de Bellefeuille et al (2001) suggested that peak use of clearcuts in southern Quebec forest was expected when Balsam Fir (Abies balsamea) and Black Spruce (Picea mariana) regeneration was 15-22 and 18-30 years old, respectively. Forest stands >15 years old were more intensively used than younger post-disturbance areas in Quebec (Jacqmain et al 2007;Hodson et al 2011), Labrador (Newbury and Simon 2005), Ontario (Thompson et al 1989), Maine (Monthey 1986), and central Alaska (Paragi et al 1997). Nevertheless, Keith and Surrendi (1971) reported Snowshoe Hare use of 1-year-old burns in central Alberta.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, specific recommendations will depend on the type of harvest employed and the age class of stands that are likely to be maintained across the landscape. Although mature, unharvested, forest stands had lower pellet counts than two of the mid-successional stand types in our study (stands that were clear-cut with site preparation and stands that were partially harvested without site preparation), we note that other researchers have found conflicting results regarding snowshoe hare abundance in older stands (e.g., Hodson et al, 2011). The relative value of older vs. mid-successional stands to snowshoe hares therefore appears complex and variable, and deserving of more research.…”
Section: Discussioncontrasting
confidence: 84%